Terahertz tunable photonic crystal optical filter containing graphene and nonlinear electro-optic polymer. (20th March 2019) - Ghasemi, Fatemeh; Entezar, Samad Roshan; Razi, Sepehr
Abstract: In this paper, new photonic crystal optical filters with very unique optical characteristics are presented. The designed structures are composed of stacked SiO2 isotropic dielectric slabs separated by monolayer graphene sheets. Defect layers of nonlinear electro-optical polymer materials are also inserted to behave as the resonant areas. Results obtained by using the transfer matrix method approach clearly reflect the possibility of the wide photonic band gap generation in the absorption spectra of the proposed crystals in the terahertz frequency range. Furthermore, a very strong relation is seen between the defect layer(s) induced resonant modes and the location/number of the defect(s) inside the crystal. To widen the scope of our findings, in addition to studying the dependencies on the structural characteristics, the tunability of the optical features using the external parameters is investigated systematically. It is shown that the number and central frequencies of the resonant modes are controllable in the far-infrared range by adjusting the temperature and wave incident angle. Thus, the proposed crystals might have remarkable applications in the fabrication of multi-channel tunable filters used in optical integrated circuits.